Weed Management in Tobacco - J. Michael Moore (EDIS)
Revised! SS-AGR-01, a 5-page fact sheet by J. Michael Moore, describes methods that should be used in an integrated weed control program for tobacco — sanitation, crop rotation, cultivation, and chemical control. Published by the UF Department of Agronomy, 2009.